1978
DOI: 10.1182/blood.v51.4.671.bloodjournal514671
|View full text |Cite
|
Sign up to set email alerts
|

Consistent activation of fetal hemoglobin synthesis in cultured adult bone marrow cells

Abstract: The production of fetal hemoglobin was investigated in plasma clot cultures of adult bone marrow cells from normal donors and from individuals with homozygous HbS or HbC disease. Synthesis of gamma and beta chains was assessed either by 35S-methionine labeling of cultures and measurement of the radioactivity incorporated into the methionine- containing tryptic peptides of the gamma and beta subunits or by 3H- leucine labeling and measurement of the radioactivity incorporated into the globin chains of Hbs F0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results pose somewhat of a conundrum, because a variety of erythropoietic stress conditions, including exposure to in vitro culture (both human and murine cells culture systems), are associated with elevated HbF levels. 35 Furthermore, it has been suggested that salubrinal-induced p-eIF2a can enhance translation of g-globin mRNA. 36,37 In contrast, our study revealed that diminished p-eIF2a is accompanied by reduced ATF4 and BCL11A levels, along with elevated g-globin transcription.…”
Section: Discussionmentioning
confidence: 99%
“…These results pose somewhat of a conundrum, because a variety of erythropoietic stress conditions, including exposure to in vitro culture (both human and murine cells culture systems), are associated with elevated HbF levels. 35 Furthermore, it has been suggested that salubrinal-induced p-eIF2a can enhance translation of g-globin mRNA. 36,37 In contrast, our study revealed that diminished p-eIF2a is accompanied by reduced ATF4 and BCL11A levels, along with elevated g-globin transcription.…”
Section: Discussionmentioning
confidence: 99%